Cervical fibroid: medical and surgical challenges faced - Pandore, Ishaan S.; Tambe, Sanjaykumar G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical fibroids are very rare accounting for 2% of all uterine fibroids. We report the case of a 48-year P4L4 with a large posterior wall cervical fibroid with a history of CVA and DVT of upper limb. Non-surgical interventional modalities like UAE were explored as a stop gap procedure. There was minimal reduction in size of mass after UAE but significant reduction in dysmenorrhoea and menorrhagia. Medical optimization of patient was achieved before definitive surgical intervention. D-J stenting of the ureters was done to prevent any injury.